Low-bandgap, highly c-axis-oriented Al-doped ZnO thin films - Long Wen (2018)
© 2017 IOP Publishing Ltd. Low-bandgap transparent conductive oxides will be of interest to researchers who wish to address the health hazards of blue radiation emission from electronic displays. Here, we present a single-step, low-temperature fast enough (throughput > 60 nm min -1 ) process to grow highly c-axis-oriented crystalline Al-doped ZnO thin films via advanced plasma processing. Dual-power DC-magnetron sputtering plasma was employed for the synthesis of thin films. The addition of top power to a pre-existing rectangular power pushed additional ions to a confined plasma and increased the plasma density and electron temperature. The effect of this additional-ion pushing was systematically studied using the microstructure, surface properties, and electronic properties. As a result, bandgap reduction from 3.35 eV to 3.10 eV and tailoring of electrical resistivity (4.89 × 10 -4 -8.32 × 10 -3 ω cm) and Seebeck coefficients (21-48 μV K -1 ) were achieved in addition to excellent transparency. Given their properties, the obtained films show promise for multifunctional applications, such as in UV and near-blue radiation shielding, transparent conductive electrodes and low-temperature thermoelectrics.